Monocytes in chronic HIV-1 infection : changes in phenotypic marker expression and their relationship with immune activation - Poovan, Karmistha (Stellenbosch : Stellenbosch University, 2015)
Thesis (MScMedSc) –Stellenbosch University, 2014.